Active Phytoconstituents for Controlling Hypercholesterolemia: A Review - Gupta RS; Rucha Lakhne; Rajnish Gupta (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2015)
Hypercholesterolemia is patho-physiological condition of metabolism caused by incessant increase in blood cholesterol levels and might be a possible risk factor for many cardiovascular and its associated diseases. Due to adverse effects and cost inefficiency of medications curing hypercholesterolemic disorders, medicinal plants are providing a cost efficient alternative to reduce the risk factors. Present review is providing data of 22 important medicinal plants species possessing antihypercholesterolemic activity and their active phyto-constituents. It would provide a ready reckoner for the research related to increased cholesterol level in blood. Further efforts should be made to implement these plant based drugs in clinical trials.